(untitled) (Altre Modernità, 2015)
This essay aims at analysing the role of the window in “A Janela”, a short story written by Lygia Fagundes Telles published for the first time in the collection O Jardim Selvagem (1965) and then republished in Antes do Baile Verde (1977). In this short story an old man returns to a room only to see the window that reminds him of his son who is dead. His reminiscences, revealed through a dialogue with the woman who lives in the room, modify the narrative structure: the transition from the present to the past discloses an introspection that makes the narration ambiguous and leads the woman – and also the reader – to suspect that the man is insane. In this way the text results in a Chinese box structure: “A Janela” contains its miniature, that is, the window which, by causing reminiscences of the man, turns out to be a sort of emblem of that “creative process” that, through the intersection of memory and fiction, defines Lygia Fagundes Telles’ literary works. Starting from the analysis of metaphorical and symbolical meanings ascribed to the window as “subject-object” of the narration, this essay will also place emphasis on the combination of memory and fiction as one of the main stylistic mark of the writer’s works in order to interpret “A Janela” as a sort of mise en abîme of the whole literary production of Lygia Fagundes Telles’.